A leaf‐level biochemical model simulating the introduction of C2 and C4 photosynthesis in C3 rice: gains, losses and metabolite fluxes. Issue 1 (13th April 2019) - Bellasio, Chandra; Farquhar, Graham D.
Summary: This work aims at developing an adequate theoretical basis for comparing assimilation of the ancestral C3 pathway with CO2 concentrating mechanisms (CCM) that have evolved to reduce photorespiratory yield losses. We present a novel model for C3, C2, C2 + C4 and C4 photosynthesis simulating assimilatory metabolism, energetics and metabolite traffic at the leaf level. It integrates a mechanistic description of light reactions to simulate ATP and NADPH production, and a variable engagement of cyclic electron flow. The analytical solutions are compact and thus suitable for larger scale simulations. Inputs were derived with a comprehensive gas‐exchange experiment. We show trade‐offs in the operation of C4 that are in line with ecophysiological data. C4 has the potential to increase assimilation over C3 at high temperatures and light intensities, but this benefit is reversed under low temperatures and light. We apply the model to simulate the introduction of progressively complex levels of CCM into C3 rice, which feeds > 3.5 billion people. Increasing assimilation will require considerable modifications such as expressing the NAD(P)H Dehydrogenase‐like complex and upregulating cyclic electron flow, enlarging the bundle sheath, and expressing suitable transporters to allow adequate metabolite traffic. The simpler C2 rice may be a desirable alternative.